Principles of tissue engineering - Lanza, Robert, 1956-; Langer, Robert S.; Vacanti, Joseph (Elsevier Academic Press, 2007)
First published in 1997, Principles of Tissue Engineering is the widely recognized definitive resource in the field. The third edition provides a much needed update of the rapid progress that has been achieved in the field, combining the prerequisites for a general understanding of tissue growth and development, the tools and theoretical information needed to design tissues and organs, as well as a presentation by the world's experts of what is currently known about each specific organ system. This edition includes greatly expanded focus on stem cells, including adult and embryonic.